Uncovering the Truth about Fake News: A Research Model Grounded in Multi-Disciplinary Literature. Issue 4 (2nd October 2021) - George, Jordana; Gerhart, Natalie; Torres, Russell
ABSTRACT: Many diverse fields across academia are interested in the fake news (FN) phenomenon. A multidisciplinary literature review can provide researchers with new insights, alternative methods, and theories from other fields. The present review incorporates FN research across fields and organizes it into three categories: FN Stimuli, the triggers and impetus for people and organizations to engage with FN; FN Actions, which encompass the activities and processes undertaken in FN; and FN Outcomes, the effects and consequences of FN Actions. Within these categories, we systematize research topics into major themes. Stimuli: motivation; Actions: fabrication, propagation, mitigation; and Outcomes: persuasion, conviction, polarization, and aversion. We identify relationships that are important in understanding the impact on society: the cycle of amplification, the cycle of fragmentation, and the progression from social polarization and aversion into motivation for more fake news. Last, we distinguish FN roles, including creators, consumers, influencers, endorsers, propagators, and resistors.